2010
DOI: 10.1002/dvdy.22480
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide exchange factor RIC‐8 is indispensable in mammalian early development

Abstract: The guanine nucleotide exchange factor RIC-8 is a conserved protein essential for the asymmetric division in the early embryogenesis in different organisms. The function of RIC-8 in mammalian development is not characterized so far. In this study we map the expression of RIC-8 during the early development of mouse. To elucidate the RIC-8 function we used Ric-8 2/2 mutant embryos. The Ric-8 2/2 embryos reach the gastrulation stage but do not develop further and die at E6.5-E8.5. We characterized the Ric-8 2/2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 57 publications
(74 reference statements)
3
27
0
2
Order By: Relevance
“…Experiments on the function of Ric8 in mammalian cells have suggested an implication in the regulation of olfactory signaling via Gαolf (47), Gq-mediated ERK activation (48), and G-proteinmediated neural function and embryogenesis (49,50). This illustrates the relevant functions of mammalian Ric-8 in the regulation of G-protein signaling and suggests a similar mechanism of Ric8-mediated excitation of Gα-protein signaling as described here for Dictyostelium.…”
Section: Ric8 Is Essential For Chemotaxis Toward Folate and Shallow Gsupporting
confidence: 54%
“…Experiments on the function of Ric8 in mammalian cells have suggested an implication in the regulation of olfactory signaling via Gαolf (47), Gq-mediated ERK activation (48), and G-proteinmediated neural function and embryogenesis (49,50). This illustrates the relevant functions of mammalian Ric-8 in the regulation of G-protein signaling and suggests a similar mechanism of Ric8-mediated excitation of Gα-protein signaling as described here for Dictyostelium.…”
Section: Ric8 Is Essential For Chemotaxis Toward Folate and Shallow Gsupporting
confidence: 54%
“…Osteoblast differentiation involves downregulation of genes associated with active proliferation and upregulation of genes involved in establishing the osteoblastic lineage (38). The Ric-8B gene encodes a GEF that has been shown to modulate G protein-dependent signaling in mitotic cells and control cell division (26,44,49,52). We found that the Ric-8B gene is strongly expressed in several osteoblastic and preosteoblastic cells that are actively proliferating.…”
Section: Resultsmentioning
confidence: 86%
“…1 I, J ). Since conventional mutations in ric-8a result in early embryonic lethality (Tõnissoo et al, 2006(Tõnissoo et al, , 2010, to determine the in vivo function of ric-8a, we used a conditional allele of ric-8a (to be published elsewhere), in which exons 2-4 are flanked by a pair of loxP sites. To delete ric-8a, we used an hGFAP-cre that targets neural progenitors as well as astroglia throughout the nervous system (Zhuo et al, 2001;Malatesta et al, 2003).…”
Section: Resultsmentioning
confidence: 99%